IZNENADNA SRČANA SMRT U SPORTU - Dikić N.; Suzić J; Dabetić M; Ostojić S.M; Mazić S; Živanić S (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Sudden cardiac death (SCD) is defined as a natural death caused by heart origins, which is characterized by sudden lost of conscience during the first hour after the onset of acute symptoms. Concomitant heart disease of varying intensity may exist but it is not necessarily the cause of death. Intensive physical activity in trained athletes with clinically significant structural changes on the myocardium accelerates progression of the disease and increases risk of SCD. Deaths on the field most often happen in intensive team sports like football and basketball in which large part of population participate. Different cardiovascular disease may cause SCD and they are related to age, sex, and race. Of those hyperthrophic cardiomyopathy is causing SCD in 36% of cases, aberrant coronary artery in 10 %, "possible hyperthrophic cardiomyopathy" in 10%, while rupture of aortic aneurism, aortic valve stenosis, other coronary anomalies, lesions caused by myocarditis, idiopathic scars, etc., are all involved in less than 10% of each.In most cases, death is caused by electrical heart instability. Several epidemiological studies showed that ventricular fibrillation (VF) is a mechanism that leads to SCD in 65- 80% of cases. Survival in ambulance VF is related to severity of the disease and the time to resuscitation. The most adequate approach to the problem of SCD is prevention. It comprises precompetition testing of the athletes and early cardiovascular disease detection. After reviewing the history and physical examination result, the physician can allow participation in sport. In the case of SCD prompt reaction is needed. Immediate resuscitation measures with the use of AED are most effective measures that can prevent fatal outcome. Because of that planning and continuous practicing of resuscitation is important part of the prevention.